Analysis of Air Distribution in a Double Tube Model Heat Exchanger System using Computational Fluid Dynamic (CFD) - Reniana, Reniana; Darma, Darma; Payung, Paulus (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The double-tube model heat exchanger has a construction of three tube cylinders arranged into one. This model of heat exchanger has a fairly simple construction, making it easier to manufacture and speeding up the manufacturing process. Computational Fluid Dynamics (CFD) is software that can be used to optimize the design and performance evaluation process as well as to speed up the process and minimize costs in tool development because it can represent phenomena that occur in a system. This research aims to analyze air distribution in a double tube model heat exchanger system using CFD analysis and to validate the analysis results with experiments. Based on the research results, a double tube model heat exchanger has been created with an average performance of output temperature and air velocity reaching 97.8oC and 10.4 m/s at a coconut shell fuel consumption of 0.24 kg/minute. The results of evaluating experimental data with simulations obtained RMSE values between 59.33 – 71.69, and MAPE values between 26.26 – 32.93. Meanwhile, the results of the Paired Sample T-Test show that there is no real difference between experimental data and simulation data with an R-value of 0.875 – 0.964. CFD analysis in this research can be used as a reference in the optimization process and development of heat exchangers, especially double-tube models. Keywords: CFD, Design, Double-Tube. Heat Exchanger, Simulation,